Life and career skills assessment for high school students - Nittayaros, Preeda; Ketchatturat, Jatuphum; Makmee, Pattrawadee (Institute of Advanced Engineering and Science, 2025)
This study assessed life and career skills among high school students in Thailand using survey research. The sample consisted of 1,050 high school students from six regions of Thailand was selected through multi-stage random sampling. The research instrument was a life and career skills assessment test for high school students and satisfaction with the life and career skills assessment for high school students. Five experts validated the instrument, which yielded a content validity index (CVI) of 0.82 and a Cronbach’s alpha coefficient of 0.89. The research results indicated that overall high school students’ life and career skills were high (M=4.50, SD=0.62). Students had a very high level of satisfaction with the overall assessment of life and career skills (M=4.59, SD=0.81). In conclusion, this life and career skills assessment can solve the problem of measuring and evaluating life and career skills for high school students. The data obtained can help school directors plan for developing the quality of students. Most importantly, the life and career skills assessment allow high school students to know the results of their own skill assessments so that they can use them to improve and develop their own skills.